On the transition of failure control from material-intrinsic defects to defects forming during monotonically increasing and cyclic mechanical loading in WC-Co hard metal at elevated temperature. (15th August 2022) - Klünsner, T.; Lube, T.; Pichler, P.; Krobath, M.; Walch, L.; Maier, K.; Ecker, W.; Marsoner, S.; Czettl, C.; Pippan, R.
Abstract: WC-Co hard metals are composite materials with extraordinary mechanical properties especially at elevated temperatures which make them common materials for metalworking tools. The current work investigates damage and fracture behavior of hourglass-shaped specimens made of a WC-Co hard metal with submicron-sized WC grains and 12 wt.% Co binder. All investigated specimens were isothermally heated inductively to 700°C in a servo-hydraulic testing machine equipped with a vacuum chamber to avoid surface oxidation. The nature of origins of fracture and the evolution of bulk material damage features was studied via scanning electron microscopy for experiments under monotonically increasing load as well as cyclic loading under a stress ratio R  =  σmin  /  σmax  = -1. A formation of small cavities that formed in the material bulk during loading was observed for all investigated loading conditions. For monotonically increasing load, the coalescence of these cavities was identified as the dominant damage mechanism. For cyclic loading, the number and size of the mentioned cavities did rise with the applied number of load cycles and rising stress amplitude. The coalescence of the cavities was found to be a main mechanism controlling the fatigue crack propagation process at elevated temperature. The found results imply that a certain combination of stress amplitude and temperature exists, at which a transition of failure control occurs from: (i) the size of material-inherent defects present prior to loading, to (ii) the kinetics of the coalescence of cavities that form due to plastic deformation and creep in the Co matrix during loading. Graphical abstract: Image, graphical abstract